Surface reconstruction on spinel oxides for oxygen evolution reaction - Luo, Songzhu (Nanyang Technological University, 2024)
In recent years, burgeoning energy demand has precipitated a marked increase in fossil fuel consumption, elevating greenhouse gas emissions and exacerbating the global climate crisis. Hydrogen has emerged as a promising next-generation energy carrier, owing to its high energy density, renewable nature, and carbon-free composition. Electrochemical water splitting constitutes a green and sustainable avenue for hydrogen generation. However, the sluggish kinetics of the oxygen evolution reaction (OER) presents a formidable impediment to efficient and large-scale hydrogen production. Among the various catalyst candidates for the OER, spinel, a type of 3d transition metal oxide, has attracted considerable attention due to their abundance and amenability to large-scale production. Surface reconstruction has been proposed as an efficacious strategy to promote the OER performance of spinel oxides. This engenders the rational design of the precatalyst, which may initiate surface reconstruction for enhanced OER performance upon specific conditioning. This dissertation endeavors to address a more profound understanding of activating catalysts through surface reconstruction. Initially, this dissertation addresses the application of chemical dissolution as a strategy to induce surface reconstruction to enhance the OER performance of NiAlxFe2-xO4 spinel oxide. Through immersion of the catalyst in a 1 M KOH electrolyte, the leaching of aluminum triggers surface reconstruction, leading to improved OER performance. Subsequently, electrochemical conditioning was applied to induce surface reconstruction. To achieve this, Cr was added to NiFexCr2-xO4 to induce reconstruction upon cyclic voltammetry (CV) conditioning by Cr leaching, resulting in superior OER performance. The best-performed NiFe0.25Cr1.75O4 exhibits a ~1500% current density increases at overpotential η = 300 mV, outperforming many advanced NiFe-based OER catalysts. It is also discovered that their OER activities are primarily determined by the Ni:Fe ratio rather than Fe content in all metal elements. The high activity and durability were also verified on a membrane electrode assembly (MEA) cell, highlighting its potential for practical large-scale and sustainable hydrogen gas generation. Besides the composition of the precatalysts, electrochemical conditioning methods and corresponding parameters may also significantly impact surface reconstruction. In the end, this thesis elucidates the impact of different electrochemical conditioning methods, namely CV and chronopotentiometry (CP), on surface reconstruction and resulting OER performance of CoFe0.25Cr1.75O4. Notably, the findings differ from prior reports on Ni-based OER catalysts, highlighting that CP conditioning potentially fosters a superior degree of surface reconstruction, thereby augmenting performance. It is posited that divergent conditioning methods may trigger distinct surface reconstruction pathways, thus influencing catalytic performance. The outcomes of this investigation not only provide a deeper comprehension of surface reconstruction but also shed light on the selection of optimal conditioning methods to enhance OER performance.